HATE SPEECH IN THE PERSPECTIVE OF INDONESIAN LAW AND ISLAMIC LAW - Syawaluddin Hanafi (IAIN Bone, 2021)
This research aims to find out the provisions of hate speech in the democratic system in Indonesia according to the provisions of the legislation in force in Indonesia and according to Islamic law. This research is a legal research that uses descriptive-qualitative method with several approaches, namely: conceptual approach, case approach, statutory approach, and comparative approach. The results of this research explain that: First, hate speech is a violation of human rights; Second, some cases of violations have damaged or killed both physically and psychologically a person; Third, sanctions in law enforcement for hate speech do not provide a deterrent effect on the perpetrators due to the lack of law enforcement, and easy problem solving because it can be done by mediation, as well as dependence on the interpretation of judges in assessing violations; Fourth, one of the principles of Islamic law (Maqasid Shari'ah) is to protect honor (hifdz nafs), it is not recommended to slander, demean others, insult, and spread false news, and Jarimah Ta'zir is a punishment for those who commit violations.